(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we consider a Lorentz space with a mixed norm of periodic functions of many variables. We obtain the exact estimation of the best M-term approximations of Nikol'skii's and Besov's classes in the Lorentz space with the mixed norm.